2021
DOI: 10.1021/acs.inorgchem.1c01600
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Mo–N–C Bond Endowed Hydrogen Evolution Reaction on MoSe2@N-Doped Carbon Hollow Nanoflowers

Abstract: Molybdenum diselenide (MoSe2) has been considered as promising electrocatalysts for catalyzing the hydrogen evolution reaction (HER) due to its narrow band gap and appropriate adsorption free energy. However, its catalytic performance is still impeded by inferior electrical conductivity and insufficient active sites, thus leading to unsatisfactory HER performance. Herein, MoSe2@N-doped carbon (NC) hollow nanoflowers with interfacial Mo–N–C bonds were controllably fabricated through the in situ selenization of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…In addition, the C 1s XPS spectrum (Figure h) provides three peaks at around 284.8, 285.9, and 289.3 eV arising from CC, CN, and CN bonds, respectively, confirming that N atoms effectively doped into the carbon matrix. The N 1s XPS spectrum (Figure i) provides four signals: graphitic N (401.78 eV), pyrrolic N (400.69 eV), pyridinic N (398.75 eV), and Cu/Mo–N species (397.40 eV), respectively. , Cu, Mo nanoparticles are tightly embedded into the Cu–Mo@NPCN composite through the formation of the Cu/Mo–N bonds . The Cu 2p spectrum shows that peak of 952.4 eV is assigned to Cu 2p 1/2 , while the peak at 932.6 eV is associated with Cu 2p 3/2 (Figure j) .…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the C 1s XPS spectrum (Figure h) provides three peaks at around 284.8, 285.9, and 289.3 eV arising from CC, CN, and CN bonds, respectively, confirming that N atoms effectively doped into the carbon matrix. The N 1s XPS spectrum (Figure i) provides four signals: graphitic N (401.78 eV), pyrrolic N (400.69 eV), pyridinic N (398.75 eV), and Cu/Mo–N species (397.40 eV), respectively. , Cu, Mo nanoparticles are tightly embedded into the Cu–Mo@NPCN composite through the formation of the Cu/Mo–N bonds . The Cu 2p spectrum shows that peak of 952.4 eV is assigned to Cu 2p 1/2 , while the peak at 932.6 eV is associated with Cu 2p 3/2 (Figure j) .…”
Section: Resultsmentioning
confidence: 99%
“…Both the peaks at 618 and 1130 cm −1 confirm the existence of MoS 2 (Mo−S) in the nanocomposites. 34 The absorption band near 1400 cm −1 , which was believed to be the result of the Mo−N bonds, 35,36 shows the most intense absorption for the MCN-20 sample, indicating the formation of abundant Mo−N bonds in that g-C 3 N 4 /MoS 2 nanocomposites.…”
Section: Experiments and Methodsmentioning
confidence: 99%
“…Density functional theory (DFT) calculations confirmed that a few proportions of the Ni atom-substituted Co site of Co 0.9 Ni 0.1 S 2 can optimize H + -adsorbed competition, hydrogen formation/desorption, and kinetics. In addition, the catalytic edge sites stemming from MoS 2 show a low Gibbs free energy for the adsorption of atomic hydrogen (Δ G H* ) like Pt-group materials . For large-scale H 2 production, water splitting is generally applied in an alkaline medium to avoid acid fog and device corrosion generated in an acidic medium.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the catalytic edge sites stemming from MoS 2 show a low Gibbs free energy for the adsorption of atomic hydrogen (ΔG H* ) like Pt-group materials. 23 For largescale H 2 production, water splitting is generally applied in an alkaline medium to avoid acid fog and device corrosion generated in an acidic medium. Nevertheless, MoS 2 shows slow kinetics in an alkaline medium.…”
Section: Introductionmentioning
confidence: 99%